十二年國教變革下高中課程與大學多元入學方案關係之研究 A Study of the Relationship between Senior High School Curriculum and the "Multiple Programs for Entrance to Universities" under the Reform of 12-Year Compulsory Education in Taiwan - 丘愛鈴 Ai-Ling Chiu (Higher Education Foundation, 2013)
在十二年國民基本教育的變革下，本研究目的有三：一、分析高中教育與大學多元入學政策目標的關係；二、探討大學二階段入學考試與高中課程實施的關係；三、探討大學甄選入學採計高中在校成績的議題。本研究主要採取焦點團體訪談、問卷調查法蒐集資料；焦點團體訪談共計有99人參加，調查對象為全國72所大學校院和72所高中的教育人員，共寄發864份問卷，回收有效問卷651份。調查資料採用次數分配、百分比統計，輔以焦點團體訪談的質性資料解釋。研究結果顯示：一、大學甄選入學有助於落實十二年國教的政策目標。二、問卷填答者中，73.9%認為繁星推薦招生名額宜在20%以下，43.6%認為個人申請入學宜在21%至40%之間，35.0%認為考試入學宜在41%至60%之間。三、大學二階段入學考試影 響高中的課程實施，宜延後學測的考試時間至高三下學期6月辦理（64.8%），並合併學測和指考為一次考試（56.4%）。四、大學甄選入學採計高中在校成績的議題，因各校教師的評分方式和標準不同（81.8%），須先強化高中教師的多元評量知能（88.2%）。依據上述研究結果，本研究提出具體建議以供教育相關單位決策 參考。 This study had three specific aims: (1) to analyze the relationship between senior high school education and the policy aims of the Multiple Programs for Entrance to Universities; (2) to explore the correlation between the university entrance examinations and curriculum implementation of senior high schools; (3) to discuss the issue of taking into account of the grade point average (GPA) from students in Personal Application Program (PAP) or School Recommendation Program (SRP) in university admission. The participants included educators from 72 universities and 72 high schools in Taiwan. Focus group discussion and questionnaire investigation were used. There were totally 99 participants in the focus group discussion and 651 valid responses for the questionnaire. The data analysis adopted the qualitative data analysis approach and statistical approaches such as frequency distribution and percentage. The major findings were as follows: (1) Most of responders had affirmative opinions for targets regarding university admission via PAP or SRP. (2) 73.9% of responders agreed to increase student enrollment ratio to 20% for SRP, and 43.6% of responders agreed to increase students enrollment ratio to 21%-40% for PAP. On the other hand, 35.0% of responders agreed to maintain students enrollment ratio to 41% to 60% for the university entrance examination program. (3) 56.4% of responders agreed to merge The General Scholastic Ability Test (GSAT) and DRT into one single test to relieve the stress of test takers. (4) 81.1% of responders agreed that score criteria (i.e., grading by teachers) vary from school to school which make it difficult to compare students' GPAs. Therefore, 88.2% of responders agreed that the assessment abilities of high school teachers should be improved. According to these findings, four suggestions were proposed for further consideration of the educational policy decision-making and execution.